Reevaluating Links Between Meteorite Impacts and Early Cenozoic Global Warming - A. Zorzi; S. M. Tikoo; G. C. Beroza; N. H. Sleep (Geophysical Research Letters)
Abstract The Paleocene‐Eocene Thermal Maximum (PETM) and the lower Chron 29n hyperthermal event were recently proposed to have been triggered by the meteorite impacts that formed the Marquez Dome (Texas, USA; 58.3 ± 3.1 Ma) and Boltysh (Ukraine; 65.39 ± 0.14 Ma) craters, respectively. We use shock physics hydrocode simulations and radiative forcing calculations to quantify the expected global temperature increase associated with impacts of different scales via the release of CO2 and CH4 sourced from target rocks into the atmosphere. Our results suggest that the <2 km diameter impactors associated with the Marquez Dome and Boltysh craters were too small to have induced hyperthermal‐like (>1 K) temperature changes, even if target rocks were carbon‐rich; >10 km diameter impactors may produce hyperthermal events, but such large impacts are predicted to be uncommon during the Cenozoic era (2–4 objects per Gyr).